METHODOLOGICAL APPROACHES TO USE ICT FOR CREATION OF THE PERSONAL EDUCATIONAL ENVIRONMENT IN THE CONTEXT OF CONTINUOUS EDUCATION - A G Muzhenskaya (RUDN Journal of Informatization in Education, 2016)
In the article the concept “educational IT-environment” based on personal network and the special features of its construction in the system of long-life education are considered, the need of construction of personal educational environment is proved, definition of this concept is given, the structure of personal educational IT-environment is proposed and means of ICT for its development are described.